FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK HOTEL DI KABUPATEN SAMBAS - B61111001, KUSNEDI (Jurnal Ekonomi Daerah (JEDA), 2019)
One of the biggest contributors to Local Revenue (PAD) of Sambas District is a local tax. Hotel tax is one of several local taxes that have a huge potential to increase regional revenue Sambas District. However, the enormous potential that can not be optimized by the local government. This study aimed to analyze the effectiveness of hotel tax as a source of Local Revenue (PAD) of Sambas District. The purpose of this study was to determine and analyze the amount of tax potential in Sambas, the level of effectiveness of tax capacity (tax-capacity) hotel in Sambas district that corresponds to the real potential of the hotel tax to increase tax revenues hotel, and the factors that affect the acceptance hotel tax in Sambas district. This research is descriptive quantitative and qualitative approaches. Quantitative methods are used to calculate the tax potential and tax effectiveness. While qualitative methods are used for technical analysis of SWOT. The population in this study is the number of hotels and inns, guesthouses and other accommodation in the district of Sambas 2012-2016. The data used is secondary data and primary data. The results of this study indicate that the Sambas District has the potential very large hotel tax and increasing every year. However, local authorities have not been able to optimize this potential, so the hotel tax revenue is not in accordance with the real situation. The results also show that tax collection in Sambas district is not effective because the results averaged below one hundred percent. However, the level of effectiveness is increasing every year. This shows the continuous improvement of government. Based on the SWOT matrix, the recommended alternative strategy is Strategy Turn-around. Management of hotel tax is in quadrant III taxation means that although the hotel has a huge opportunity, but on the other hand faces several constraints or internal weaknesses. It required the Turn-around strategy that minimizes internal problems so that it can seize better opportunities (Weaknesses-Opportunities Strategy). Keywords: Local Revenue (PAD), Potential of Hotel Tax, Effectiveness of Hotel Tax, SWOT